2013
DOI: 10.1159/000354435
|View full text |Cite
|
Sign up to set email alerts
|

BMP15 Prevents Cumulus Cell Apoptosis Through CCL2 and FBN1 in Porcine Ovaries

Abstract: Background: Bone morphogenetic protein-15 (BMP15) is a maternal gene necessary for mammalian reproduction. BMP15 expression increased in oocytes accompanied by follicle growth and development. The function and regulation mechanism of BMP15 in porcine cumulus cell apoptosis process is still unclear now. Methods: In this study, flow cytometry (FCM) was used to analyze the effects of BMP15 with different concentrations to cumulus cell apoptosis. High-throughput sequencing technology was carried out to screen reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
2
32
0
2
Order By: Relevance
“…BMP15 can significantly inhibit cumulus cell apoptosis and promote their proliferation by inducing the expression of hyaluronidase 2 (HAS2), pentraxin 3 (PTX3) and prostaglandin synthase 2 (PTGS2) to optimize the oocyte microenvironment and drive oocyte maturation and ovulation [5-8]. GDF9 also has a similar function to that of BMP15 and can inhibit the expression of the LH/CG receptor (LHCGR) and KIT ligand in cumulus cells, inducing the expression of cumulus cell proliferation-related genes and promoting oocyte maturation and ovulation [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…BMP15 can significantly inhibit cumulus cell apoptosis and promote their proliferation by inducing the expression of hyaluronidase 2 (HAS2), pentraxin 3 (PTX3) and prostaglandin synthase 2 (PTGS2) to optimize the oocyte microenvironment and drive oocyte maturation and ovulation [5-8]. GDF9 also has a similar function to that of BMP15 and can inhibit the expression of the LH/CG receptor (LHCGR) and KIT ligand in cumulus cells, inducing the expression of cumulus cell proliferation-related genes and promoting oocyte maturation and ovulation [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…As an oocyte-secreted factor, BMP15 serves a crucial role in follicular growth and oocyte quality, which is underexpressed in PCOS patients. Adding BMP15 to cultures significantly reduced the apoptosis of granulosa cells (9,(28)(29)(30). Therefore, it is of value to investigate the effect of BMP15 on the apoptosis of granulosa cells in PCOS (11,12,31).…”
Section: Discussionmentioning
confidence: 99%
“…BMP15 is one of the TGFB family members, which is a well-known oocyte-secreted growth factor that acts on cumulus cells to regulate multiple functions, such as the proliferation, expansion, and apoptosis of cumulus cells (Sudiman et al, 2014). Previous high-throughput sequencing results from our group demonstrated that BMP15 increased FAT1 mRNA (Zhai et al, 2013). Studies have demonstrated that the FAT1 gene encodes a v-3 fatty acid desaturase enzyme that converts v-6 to v-3 polyunsaturated fatty acids (PUFAs) and thus increases v-6/v-3 ratio (Chen et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 96%